Analisis Koneksi Matematika Ditinjau dari Tipe Kepribadian Sanguinis, Koleris, Melankolis, dan Plegmatis - Dewi Anggreini; Eko Priyojadmiko; Dwi Setiana (Universitas PGRI Adi Buana Surabaya, 2020)
Mathematics is a subject that has the concept of interrelation between one material with another. Understanding the interrelated material required the existence of a basic ability that is the ability to connect mathematics. The obstacle experienced by students is that when given a problem and the solution is related to the previous material, students are unable to remember the material that is the key to solving the problem. The inability of students is due to lack of memory of previous material and students pay less attention when the teacher is explaining in class. Personality differences make students have different mathematical connection abilities. The purpose of this study is to describe the ability of students' mathematical connections in terms of sanguinis, koleris, melancholy, and plegmatic personality types. This type of research is a qualitative descriptive study in the form of case study research. Methods of data collection used personality type questionnaires, math connection test questions, and interviews. The results showed that the sanguinis and plegmatic personality types were able to meet all the connection indicators. Koleris personality type is able to fulfill 4 indicators. Melancholy personality types produce different connection capabilities, namely the ability of connections that meet 4 indicators and 1 indicator. This research can provide benefits for students to improve their mathematical connections and understand their personality types. Students who understand their personality types can minimize negative traits that inhibit mathematical connections.